Au-delà d'une certaine lecture standard DE La Grande Transformation - Plociniczak, Sébastien (Revue du MAUSS, 2007)
Whereas a largely conveyed standard reading of The Great Transformation lets one think that Karl Polanyi establishes the effective birth certificate of a self-regulated market at the nineteenth century in the West, this text suggests that The Great Transformation makes Polanyi the author of a criticism of the theoretical fiction of the self-regulated market, and the historian of this acting fiction which directs individual behaviors and transforms in-depth the Western societies of the nineteenth century.
Economics
Keywords: Great Transformation; The (Book); great transformation; reinterpretation